Identifying the approach to financial sustainability: Navigating the complexities of earning and spending - Alam, Naushad; Shahfaraz Khan, Mohammad; Azad, Imran; Shahid, Faisal; Ahmad Dar, Amir (Edelweiss Applied Science and Technology, 2024)
This study provides insightful information about personal finance by examining the complex relationship between income and spending patterns in various occupations. It reveals strong relationships between income levels and expected results through regression analysis, providing insight into how different occupational groups are impacted by financial well-being. Building on this basis, a thorough one-way ANOVA and post-hoc tests show that students, academics, labourers, business owners, and government employees have remarkably different spending preferences. These results highlight the significant impact of occupation-specific variables on financial behaviour, including benefits, income stability, and social expectations. This research provides a path corresponding to specific policy interventions and programs aimed at financial literacy. By promoting economic resilience and well-being across a range of demographic and occupational landscapes, the ultimate objective is to cultivate a future in which responsible spending practices are shared realities rather than just ideals.